SUSTAINABILITY OF LANGKAT MALAY LANGUAGE A STUDY OF COMMUNITY OF YOUNG PEOPLE IN STABAT, LANGKAT REGENCY - Adisaputera, Abdurahman; Suastra, I Made; Jendra, I Wayan; Budiarsa, Made (e-Journal of Linguistics, 2010)
This study explores the sustainability of the Langkat Malay Language (Bahasa MelayuLangkat abbreviated as BML) spoken by the speech community of young people based on languagechoice, language attitude, language dynamics and influential socio- cultural and socio-ecologicalfactors. 230 (two hundred and thirty) young people were used as the samples in this study. The dataneeded were obtained by documentation, survey, interview, and participatory observation methods.The findings show that there was a shift from BML to Indonesian language (BahasaIndonesia abbreviated as BI) in every domain of use and in various situations of communication.As far as BML is concerned, some internal shifts were also found. The intention to adjust the BMLforms to the forms and meanings of BI in phonological, lexical and grammatical levels wasresponsible for this. Both the internal and external factors led to the shifts of BML to BI. Theinfluential internal factors included (1) high tolerance of other ethnic groups; (2) high socialmobility of the young people; (3) the decrease in cultural traditional activities; (4) the decrease inthe concept of Mel ecology; (5) the attitude of not being observant to BML, and (6) no simultaneitybetween traditional processions and the BNL use. The external factors included (1) the new comingethnic groups, especially the ethnic group of Eja, were getting more dominant; (2) the residingpattern was getting mixed; (3) as the National Language, BI was more widely used, understood bybilinguals, gave prestige in social intercourse; and (4) there was a high interaction between thecommunity of young people and the other communities coming from different ethnic groups andspeaking different languages. Ecologically, the domains of meanings referring to particularreferents in BML went down as far as the concepts of its speakers are concerned. Such a fallresulted from (1) the limited interaction between the community of young people and the Melecology-featured entities; (2) the entities were so scarce that they were not included in the speakers’minds; (3) and the lexical concepts internalized by the speakers, as far as those entities areconcerned, were excluded in BML but included in the other languages. The shift from BML to BImade by the young speakers made BML get highly less sustainable. By referring to the criteriaintroduced by Wurm (in Crystal, 2000: 20) concerning the extinction of languages, it may be statedthat BML is already in stadium 2, that is, a language which is almost getting extinct.
Keywords: sustainability, domain, language choice, language attitude, river ecology, Malay community, young people, language shift.